Необычные свойства обычных металлов - Займовский Владимир Александрович (Библиотечка "Квант", 1984)
Экземпляры: (20181220) / Инвентарный номер: 11905 / Цена: 0.30 / Сис.шифр: 530.1 / Авт.знак: З-17 / ББК: 530.1